Fatores sociodemográficos de brasileiros e a não procura pela atenção primária à saúde bucal no SUS - Lis Anete Cornélia Campos Gomes (2020)
This study analyzed the socio-demographic factors that influence SUS users not to seek oral health services in Primary Health Care. Database of Brazilian Ministry of Health’s National Program for Improving Access and Quality in Basic Care (PMAQ - AB) 3rd Cycle (2017-2018) was analyzed. Data collection instruments were answered by users of primary health care units (PHCU) in 5.324 cities across the country. In each health unit four adult users were interviewed by trained researchers. Among 144,440 interviewed users, 117,570 were in PHCU which included family health strategy teams and family oral health teams (self/eSB). Study variables were obtained from PMAQAB module III - user interview: user Identification and access to care. It included independents variables on user’s sociodemographic profile (gender, age group, marital status, self-declared skin color, schooling, per capita income, and being beneficiary of basic income public programmer (PBF). Dependent variables were lack of demand or access to POHCS. Bivariate analysis, gross, and multiple logistic regression using SATA version 15.0 were performed to identify association between variables. Among the 117.570 participants, 48.82% (n = 57.403) reported being able and 4.01% (n = 4718) reported not being able to make a dental appointment. The remaining 47.16% (n = 55.449) had never sought POHCS in the PHCU. The highest chance of not seeking POHCS was observed among widowed individuals, the elderly, those with higher income and those with lower schooling. Users with lower chances of not seeking POHCS, were self-reported black, brown, yellow, and of indigenous skin color, presented higher schooling and were beneficiaries of PBF. Lack of demand for POHCS was associated with user’s socio-demographic characteristics. Dental health teams should target inequalities in services access, develop strategies to actively search missing users, and enhance POHCS access.